Photocatalytic activity under visible light of Fe-doped CeO2 nanoparticles synthesized by flame spray pyrolysis - Channei D. (2014)
CeO2 nanoparticles (undoped and Fe-doped) were synthesised using flame spray pyrolysis with varying Fe-dopant concentrations. X-ray diffraction analysis revealed the absence of any impurity phases in all samples. BET (Brunauer, Emmett and Teller) tests showed that the average sizes of undoped and Fe-doped CeO2 particles were 6.39 and 5.94 nm, respectively. Specific surface area of the particles increased with increasing Fe-dopant concentration. High resolution transmission electron microscopy (HRTEM) revealed that the nanoparticles were either spherical or equiaxed in shape. UV-vis spectroscopy showed a shift of the adsorption edge towards longer wavelengths along with a decrease in the optical indirect band gap from 3.18 to 2.90 eV for undoped particles and 2 mol% Fe-doped particles. In terms of photocatalytic performance, Fe-doped CeO2 nanoparticles were responsible for an increased degradation of the carbon from formic and oxalic acids. Furthermore, the photocatalytic efficiency was ∼100% when 2 mol% Fe-doped CeO2 particles were used for testing. © 2012 Elsevier Ltd and Techna Group S.r.l.